Analisis Risiko Operasional Dengan Metode FMEA - Dewi Cahyani Pangestuti; Heni Nastiti; Renny Husniaty (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2022)
One of the failures in starting a business is failure in poor operational management. Operational risk is caused by internal process failures, human errors, system failures or external problems that affect operational activities. This study aims to measure the operational risk of PT. Unilever Tbk. before and during the Covid 19 pandemic. The method used is qualitative, with data collection techniques used, namely observation and documentation techniques. The results of this study there are differences in the level of RPN on internal and external failures. If before the pandemic operational risk – external was the lowest risk crisis, during the Covid 19 pandemic, operational risk – internal was the lowest risk crisis. Lack of working capital and increased spending caused by the pandemic. Investors are less interested in consumer stocks and the provision of a new normal kit increases the company's expenses without being accompanied by income. Operational-external risk also increases due to the risk of late arrival of raw materials and disruption to the supply chain network, especially at suppliers.